Social protection of homeless children in industrialized regions of Ukraine in 1917-1920 - Viacheslav Popov (Cхід, 2013)
In the offered article on the basis of the archived documents basic directions on which in 1917-1920 inthe south-east districts ofUkrainethe social help was carried out minor are considered, remaining without the care of parents. The basic forms of social help are adopted, state organs and public organizations carrying out the given function are definite, the dynamics of social defence of children on different stages of the studied period is analysed.